Environmental Critical Analysis of Urban Heat Island Phenomenon Using ECI (Environmental Critically Index) Algorithm in Surakarta City and Its Surroundings - Helen Cynthia Aprilia; Andri N.R. Mardiah; Jumadi (International Journal for Disaster and Development Interface, 2021)
One of the impacts of unplanned urban growth is the decrease of urban vegetation which is replaced by land development such as buildings, roads and open land with paving block materials. This causes the environmental quality to decline. Surakarta City is one of the cities with rapid growth in Central Java. This is indicated by the increase in population over the years. This research examines the phenomenon of changes in environmental quality using ECI with variables NDVI and LST using Landsat 8 in 2013 and 2019. In particular, this study analyzes the relationship between ECI and UHI and the relationship between LST and NDVI to ECI. The results show that in 2013 ECI area was dominated by the City Center, then in 2019 it expanded to the outer areas surrounding Surakarta City. The Urban - Rural gradient also illustrates that the highest average of ECI in urban areas will decrease when heading to Rural areas. The decrease happened due to the pressure from the growing population. Each variable has a strong correlation with one another and influences each other. Efforts to overcome environmental criticality are sustainable greening, because green spaces can help reduce the warming effects of UHI.